Does Renewable Energy Consumption a Driver for Economic Growth? Panel Data Analysis in Selected OIC Countries - Pratomo, Wahyu; Rusydiana, Aam; Riani, Ririn; Lubis, Rukiah; Marlina, Lina; Putra, Purnama; Nurismalatri, Nurismalatri (International Journal of Energy Economics and Policy, 2023)
This paper aims to examine the relationship between energy consumption from renewable energy sources, and economic growth expressed in GDP per capita in several OIC countries. The dataset used involves data from OIC (Organization of Islamic Cooperation) countries including Indonesia, Iran, Turkey, Saudi Arabia, Nigeria, Egypt, UAE, Malaysia, Bangladesh, and Pakistan for the period 2000 to 2018 obtained from the World Development Index. This study uses a dynamic panel estimation approach such as DOLS and FMOLS to determine the long-term relationship between variables. We also discuss how to use the panel Granger-causality test to estimate causality in the short term. The empirical result shows that in the long-run, renewable energy consumption doesn't have an effect on economic growth. Meanwhile, CO2 emissions were found to have a significant positive relationship with economic growth. Furthermore, the conservation hypothesis theory is accepted between economic growth and consumption of renewable energy. Thus, the implementation of conservation policies can be applied by taking into account economic growth.